2022
DOI: 10.3389/fphys.2022.1034014
|View full text |Cite
|
Sign up to set email alerts
|

Through network pharmacology and molecular docking to explore the underlying mechanism of Artemisia annua L. treating in abdominal aortic aneurysm

Abstract: Background: Abdominal aortic aneurysm (AAA) is a degenerative disease that causes health problems in humans. However, there are no effective drugs for the treatment of AAA. Artemisia annua L. (A. annua) is a traditional herbal that has been widely used in cardiovascular disease. Based on network pharmacology and molecular docking technology, this study predicted the practical components and potential mechanisms of A. annua inhibiting the occurrence and development of AAA.Methods: The main active ingredients an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…Through these methods, the underlying mechanism of A. annua in the treatment of abdominal aortic aneurysm was found. 25 In addition, a large number of articles on network pharmacology have been published, which are devoted to elaborating the mechanism of action of TCM. In China, A. annua has been used as herb for treating various diseases for thousands of years.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Through these methods, the underlying mechanism of A. annua in the treatment of abdominal aortic aneurysm was found. 25 In addition, a large number of articles on network pharmacology have been published, which are devoted to elaborating the mechanism of action of TCM. In China, A. annua has been used as herb for treating various diseases for thousands of years.…”
Section: Discussionmentioning
confidence: 99%
“… 44 Additionally, some studies have shown that kaempferol induces G2/M phase cell cycle arrest and apoptosis, inhibits cell invasion, and upregulates the m-TOR/PI3K signaling pathway, thus contributing to the suppression of endometrial cancer. 45 Furthermore, luteolin, 25 isorhamnetin, 46 artemetin, 25 and stigmasterol 47 have been found to inhibit the proliferation of endometrial cancer cells. Subsequently, we performed molecular docking of PTGS2 with quercetin, kaempferol, luteolin, isorhamnetin, artemetin, and stigmasterol and found that all of these components exhibited strong binding activity with PTGS2, with an affinity value smaller than −7.0 kcal/mol.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations